A guide to the polycystic ovary its effects on health and fertility - Kovacs, Gabor; Smith, Jane, 1954- (Tfm Pub., 2002)
Several studies have looked at populations of volunteers, women from the electoral roll and women attending general practices, and have reported the ultrasound appearance of polycystic ovaries in as many as one in three to one in five. This book also looks at the historical background of this condition; lifestyle factors; and pregnancy outcomes.